Scientometric Insights into Rechargeable Solid-State Battery Developments - Raj Bridgelall (World Electric Vehicle Journal)
Solid-state batteries (SSBs) offer significant improvements in safety, energy density, and cycle life over conventional lithium-ion batteries, with promising applications in electric vehicles and grid storage due to their non-flammable electrolytes and high-capacity lithium metal anodes. However, challenges such as interfacial resistance, low ionic conductivity, and manufacturing scalability hinder their commercial viability. This study conducts a comprehensive scientometric analysis, examining 131 peer-reviewed SSB research articles from IEEE Xplore and Web of Science databases to identify key thematic areas and bibliometric patterns driving SSB advancements. Through a detailed analysis of thematic keywords and publication trends, this study uniquely identifies innovations in high-ionic-conductivity solid electrolytes and advanced cathode materials, providing actionable insights into the persistent challenges of interfacial engineering and scalable production, which are critical to SSB commercialization. The findings offer a roadmap for targeted research and strategic investments by researchers and industry stakeholders, addressing gaps in long-term stability, scalable production, and high-performance interface optimization that are currently hindering widespread SSB adoption. The study reveals key advances in electrolyte interface stability and ion transport mechanisms, identifying how solid-state electrolyte modifications and cathode coating methods improve charge cycling and reduce dendrite formation, particularly for high-energy-density applications. By mapping publication growth and clustering research themes, this study highlights high-impact areas such as cycling stability and ionic conductivity. The insights from this analysis guide researchers toward impactful areas, such as electrolyte optimization and scalable production, and provide industry leaders with strategies for accelerating SSB commercialization to extend electric vehicle range, enhance grid storage, and improve overall energy efficiency.